An Experimental And Theoretical Vibrational Spectroscopic Study On Niflumic Acid, A Non-Steroidal Anti-İnflammatory Drug - Balcı, Kubilay; Akkaya, Yasemin; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
The theoretically possible stable conformers of niflumic acid (NFA) molecule in electronic ground state were investigated by means of potential energy surface scan and thermochemistry calculations carried out at room temperature using DFT-B3LYP method and different Pople-style basis sets. The data obtained from these calculations confirmed that the two planar conformers in which the carboxyl and fluoromethyl functional groups are located either in "trans" or in "cis" position to each other are the most favorable ones in energy among all the stable conformers of the free molecule. This conclusion was also confirmed by the energy values obtained from the higher-accuracy thermochemistry calculations carried out using G3MP2B3 composite method. For both conformers and also for their most favorable dimer forms in energy, the equilibrium geometry, force field and vibrational spectral data were calculated first at B3LYP/6-31G(d) and then at B3LYP/6-311++G(d,p) levels of theory. On the basis of these theoretical data, the effects of the conformation and dimerization on the corresponding experimental data of NFA molecule were discussed in detail. The overestimations of the calculated harmonic wavenumbers were corrected by the aid of two different empirical scaling procedures referred to as "scaled quantum mechanical force field (SQM FF) methodology" and "dual scale factors". In the light of the improved theoretical data obtained in these two approaches applied independently from each other, a successful assignment of the fundamental bands observed in the room-temperature IR and Raman spectra of the molecule was given. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Niflumic acid (NFA); IR and Raman spectra; Vibrational modes; Dual scale factors; Scaled quantum mechanical force field (SQM FF); Density-Functional Theory; Mechanical Force-Fields; Raman-Spectra; Scaling Factors; Breast-Cancer; Molecular Geometries; Chloride Channels; Band Assignment; Hartree-Fock; Frequencies; titreşim modları; Çift ölçek faktörleri; Ölçeklendirilmiş kuantum mekaniksel kuvvet alanı; Yoğunluk-Fonksiyonel Teorisi; ölçekleme faktörler; Meme kanseri; moleküler geometriler; klorür kanalları; frekanslar